Antioxidant Activity of New Tetrazole, Thiazolidin-4-one, and Aza-beta Lactam Linking to Secondary Imines of Imidazopyridine - Abdul Maged, Abdul Gabar; AL-Lami, Naeemah (Iraqi Journal of Science, 2024)
In this contribution, new derivatives of bicyclic fused rings with a bridgehead nitrogen atom were synthesized from the imidazo[1,2-a]pyridine derivatives C1 by reacting two moles of 2-aminopyridine and 4-aminoacetophenone with iodine in a one-pot reaction. This compound (C1) was then condensed with 2-nitrobenzaldehyde and 2,4-dichlorobenzaldehyde to form new derivatives of Schiff bases (C2 and C3). These Schiff bases were then cyclized to synthesize thiazolidin-4-one derivatives (C4 and C5), tetrazole derivatives (C6 and C7), and aza-β-lactam derivatives (C8 and C9) through the reactions with thioglycolic acid, sodium azide, and 1-naphthylisocyanate, respectively. FT-IR, 1H NMR, and 13C NMR spectroscopy were used to characterize these new compounds. In the second part of this work, the antioxidants of these compounds were measured, and results ranged from good to medium.